5/6x-8=-3

Simple and best practice solution for 5/6x-8=-3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 5/6x-8=-3 equation:



5/6x-8=-3
We move all terms to the left:
5/6x-8-(-3)=0
Domain of the equation: 6x!=0
x!=0/6
x!=0
x∈R
We add all the numbers together, and all the variables
5/6x-5=0
We multiply all the terms by the denominator
-5*6x+5=0
Wy multiply elements
-30x+5=0
We move all terms containing x to the left, all other terms to the right
-30x=-5
x=-5/-30
x=1/6

See similar equations:

| x=195.5*130 | | 3.1=9.8z | | 2+13=-5{6x-3} | | 9x-91+6x-76=180 | | 5m+14=3m+2 | | 7y+8=8y-2y | | 8=-(4/9)u | | 2+2x+1=-1 | | 6x+17+10x-27=180 | | -4(b+2)-6b=-40-6b | | 1/3m+2/3m=0 | | 130=5(6÷5v) | | 2(p+4)^2+5(p+4)+5=0 | | X+15+x+16=21 | | 0=-3v+2 | | 7y-9-4y=4y-7 | | 8+2x-1=9x | | 8x+15=6x+9 | | 2(4+-1)+3=5t+4+3t | | 2-11+2x=x+2 | | 2(4z-1)=3(7+2) | | 2x+11+2x+3=14 | | 6g+20=2g+28g | | 5m-14=3m+2 | | 78=x+6x+8 | | X-1+x+4=19 | | 5(y+5)-8y=13 | | f(4)=3-^4 | | -8(1-5p)=-8-8p | | f(4)=3-2 | | 10+2x-14=x+4 | | g(529)=6(529^2)+36(529)−17 |

Equations solver categories